The ABCs of Financial Education: Experimental Evidence on Attitudes, Behavior, and Cognitive Biases - Carpena, Fenella; Cole, Shawn; Shapiro, Jeremy; Zia, Bilal (Management Science, 2019)
This paper uses a large-scale field experiment in India to study attitudinal, behavioral, and cognitive constraints that can stymie the link between financial education and financial outcomes. The study complements financial education with (i) financial incentives on a financial literacy test to affect participant motivation, (ii) financial goal setting to provide a psychological nudge, and (iii) personalized financial counseling to enhance the intensity of treatment. The analysis finds no impact of financial incentives on learning but significant effects of both goal setting and counseling on real financial outcomes. These results identify important complements to financial education that can bridge the gap between financial knowledge and behavior change. Data and the online appendix are available at https://doi.org/10.1287/mnsc.2017.2819 . This paper was accepted by Amit Seru, finance.